Розвиток історико-краєзнавчої бібліографії в Криму (20–30-ті роки ХХ століття) - Назарчук, Т. (Краєзнавство, 2009)
Викладені передумови розвитку краєзнавчої бібліографії в Кримській АРСР, виділені її відмінні риси. Схарактеризована діяльність видатного історика, ученого-краєзнавця А. І. Маркевича. Висвітлений внесок у розвиток історико-краєзнавчої бібліографії Криму бібліографів В. В. Симоновського, Д. М. Єгорова, Д. С. Спиридонова, Ф. П. Максименка та ін. Изложены предпосылки развития краеведческой библиографии в Крымской АССР, выделены ее отличительные черты. Рассмотрена деятельность выдающегося историка, ученого-краеведа А. И. Маркевича. Дан анализ его фундаментального труда “TAURICA”, который является одним из ключевых историко-краеведческих пособий, созданных в период существования Крымской АССР. The prerequisites of the development of regional bibliography in the Crimean ASSR are presented, its distinguishing features are allocated. The activity of the outstanding historian, scientist- student of local lore A. I. Markevich is examined. There is the analysis of its fundamental work “TAURICA”, which is one of the key historic- regional textbook, created in the time of Crimean ASSR. There is the characteristic of indicators by V. V. Simonovskiy — “bibliography of krymovedeniya”. The contribution to development of the historic- regional bibliography of Crimea the bibliographers D. N. Yegorov, D. S. Spiridonov, F. F. Maksimenko and others is illuminated.